Presowing treatment of seeds as an element of management of the productive potential of winter wheat - Маренич, М. М. (Scientific Progress & Innovations, 2017)
The results of studies on the use of disinfectants and humates for presowing seed treatment are presented. It was found that the introduction of humates in a mixture with preservatives naturally increased the field germination and the number of nodal roots compared to the control. Average annual indices testify to the natural effect of the use of stimulants on the reduction of the period of «sowing–shoots», but under adverse conditions of germination the use of stimulants can play a very important role in obtaining amicable shoots. In the case of application of humates, the field germination of seeds increased by 11–13 %. Under unfavorable conditions prevailing during the germination period, the effect of the factors increased and the influence of such interactions as «precursors–grade» and «variety–variant of seed treatment» increased. The formation of nodal roots also significantly depended on the variant of seed treatment. The best indicator was a variant of the experiment, where «1R Seed treatment» was used, which subsequently significantly influenced the formation of yields. In all the experiments conducted, the positive effect of the use of stimulants «Humifield» and «1R Seed treatment» for seed treatment, both in mixtures with disinfectants, and in cases where they were used separately, was noted.